2019
DOI: 10.1080/10643389.2019.1565519
|View full text |Cite
|
Sign up to set email alerts
|

The contrasting roles of science and technology in environmental challenges

Abstract: Sustainable development is widely recognized as an existential challenge. To address it, humanity needs to change its ways. However, people seem slow to act, not always understanding and often denying environmental imperatives, creating substantial social and psychological barriers. Social inertia and denial have been allegedly amplified by a public discourse increasingly distrustful of science. But is this discourse a rejection of science or an erosion of trust in how science is applied? The paper examines th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 122 publications
0
31
0
2
Order By: Relevance
“…Emerging transition pathways such as repurposing of waste, which involve fundamental changes in chemical life cycles need incentives. • Encourage multi-stakeholder involvement in EU collaborative projects to capture added value and address complexity Solution-oriented research needs to go beyond the scientific community and needs to engage with the private sectors, governments, citizen groups and environmental organizations [12]. Multiple stakeholder participation in ambitious integrated research projects can play several roles.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging transition pathways such as repurposing of waste, which involve fundamental changes in chemical life cycles need incentives. • Encourage multi-stakeholder involvement in EU collaborative projects to capture added value and address complexity Solution-oriented research needs to go beyond the scientific community and needs to engage with the private sectors, governments, citizen groups and environmental organizations [12]. Multiple stakeholder participation in ambitious integrated research projects can play several roles.…”
Section: Recommendationsmentioning
confidence: 99%
“…The EU strategy for a non-toxic environment (http:// ec.europ a.eu/envir onmen t/ chemicals/non-toxic/index_ en.htm) responds to these challenges and provides an ambitious commitment in support of goals, geared towards the provision of food (SDG 2), clean water for humans (SDGs 3 and 6), responsible production and consumption (SDG 12), as well as safeguarding of aquatic life (SDG 14). Furthermore, as the SDGs are interconnected [12], integrated environmental policies and strategies are required to protect our natural capital, stimulate resource-efficient, low-carbon growth and innovation, safeguard people's health and well-being while respecting the Earth's natural limits [13].…”
mentioning
confidence: 99%
“…Environmental management refers to scientific and professional research related to habitat conservation, hazard control, monitoring, use, and conservation of various natural resources. Scientists and experts from different scientific fields and branches of science are involved in scientific and professional environmental research (Voulvoulis, Burgman, 2019). Besides biophysical sciences, important components of environmental management are the socio-economic and governance regulatory aspects.…”
Section: (P5) Environmental Managementmentioning
confidence: 99%
“…Furthermore, the study revealed that these environmental changes stem from problems in environmental objects and subjects that are responsible for the sustainability of the environment itself (Brookfield, 1999). Various factors are indicated as triggers of environmental problems such as climate change (Blennow, Persson, Tomé, & Hanewinkel, 2012;Clavero, Villero, & Brotons, 2011), changes in natural resources (Jacobs & Brown, 2014), technological change and development (Voulvoulis & Burgman, 2019), the presence of pollution (Wiessner et al, 2014), and the most crucial factor is human activities (Li & Wu, 2019). Human activities are said to be crucial factors due to their role as agents of environmental preservation (Short, 2009).…”
Section: Introductionmentioning
confidence: 99%